Torak ki talash - Saleem ahmed sadiquie (Ferozsons (Pvt) Limited ; Lahore)
"Torak Ki Talash" is an adventurous tale of determination and resilience, following the protagonist's relentless journey to uncover hidden truths and achieve a long-sought goal.